Design and verification of a single-degree-of-freedom driven deformable wheel mechanism - C. Sha; Y. Huang; Y. Wang; B. Wang; F. Zhou; G. Zhang (Mechanical Sciences)
Improving the obstacle-crossing ability of special vehicles in complex environments is essential for emergency rescue and security operations. To address this need, a single-degree-of-freedom driven deformable wheel mechanism is proposed, which enables efficient wheel diameter adjustment and a high expansion ratio. First, the degrees of freedom of single-vertex and multi-vertex origami mechanisms are analyzed using the Jacobian matrix method, and then a kinematic model is developed using the improved Denavit–Hartenberg (D–H) method to provide theoretical support for the motion characteristics. Next, a comprehensive performance analysis is conducted, including evaluations of stiffness, expansion ratio, and motion. The mechanism's reliability and adaptability are verified through finite-element and dynamic simulations. In the experimental phase, a prototype of the deformable wheel is fabricated using additive manufacturing technology, and the selected resin material not only ensures excellent processing and shaping properties but also offers a lightweight design and structural stability, effectively enhancing the wheel's expansion performance and overall stiffness. Finally, through expansion ratio testing and performance verification, experimental results demonstrate that the proposed mechanism design features fewer driving components, a high expansion ratio, and strong environmental adaptability. This study provides a possible solution for the design of deformable wheels from the perspective of the feasibility of deployable mechanisms.